Automation of knowledge asset in Public Works Department (PWD) of Malaysia - Jusoh, Yusmadi Yah (2004)
Finding the right information quickly and easily to make informed decisions is one of the biggest challenges faced by PWD today.To automate the management of the knowledge assets, PWD have to stand back and take a strategic approach – to understand why and where knowledge management (KM) will deliver the greatest benefits.Knowledge not so many years ago was based on paper filing, and PWD depended on knowledgeable workers who knew how it was filed, and had experience that enabled them to make ‘informed’ decisions.Today, this has all changed as information is held electronically and often needs to be shared with others beyond the traditional boundaries of the corporation.The objective is to make pilot study on the automation of the knowledge asset based on Knowledge Management in Project Monitoring System Unit, Information Technology Centre, Corporate Management Branches of PWD by leveraging on the existing Information Technology Infrastructure available.The outcome of the study will be presented to the Director of Corporate Management Branches of Public Works Department (PWD) as a pilot project.